Secondary attack rate of tuberculosis in urban households in Kampala, Uganda. - Christopher C Whalen; Sarah Zalwango; Allan Chiunda; LaShaunda Malone; Kathleen Eisenach; Moses Joloba; W Henry Boom; Roy Mugerwa (PLoS ONE)
Background Tuberculosis is an ancient disease that continues to threaten individual and public health today, especially in sub-Saharan Africa. Current surveillance systems describe general risk of tuberculosis in a population but do not characterize the risk to an individual following exposure to an infectious case. Methods In a study of household contacts of infectious tuberculosis cases (n = 1918) and a community survey of tuberculosis infection (N = 1179) in Kampala, Uganda, we estimated the secondary attack rate for tuberculosis disease and tuberculosis infection. The ratio of these rates is the likelihood of progressive primary disease after recent household infection. Results The secondary attack rate for tuberculosis disease was 3.0% (95% confidence interval: 2.2, 3.8). The overall secondary attack rate for tuberculosis infection was 47.4 (95% confidence interval: 44.3, 50.6) and did not vary widely with age, HIV status or BCG vaccination. The risk for progressive primary disease was highest among the young or HIV infected and was reduced by BCG vaccination. Conclusions Early case detection and treatment may limit household transmission of M. tuberculosis. Household members at high risk for disease should be protected through vaccination or treatment of latent tuberculosis infection.